Ionized Gas Outflows in the Galaxy and Mass Assembly (GAMA) Survey: Signatures of AGN Feedback in Low-mass Galaxies - Sheyda Salehirad; Amy E. Reines; Mallory Molina (The Astrophysical Journal)
We present a sample of 398 galaxies with ionized gas outflow signatures in their spectra from the Galaxy and Mass Assembly Survey Data Release 4, including 45 low-mass galaxies with stellar masses M _*  < 10 ^10 M _⊙ . We assemble our sample by systematically searching for the presence of a second velocity component in the [O  iii ] λλ 4959, 5007 doublet emission line in 39,612 galaxies with redshifts z  < 0.3. The host galaxies are classified using the Baldwin–Phillips–Terlevich diagram, with ~89% identified as active galactic nuclei (AGNs) and composites and 11% as star-forming (SF) galaxies. The outflows are typically faster in AGNs with a median velocity of 936 km s ^−1 compared to 655 km s ^−1 in the SF objects. Of particular interest are the 45 galaxies in the low-mass range, of which a third are classified as AGNs/composites. The outflows from the low-mass AGNs are also faster and more blueshifted compared to those in the low-mass SF galaxies. This indicates that black hole outflows can affect host galaxies in the low-mass range and that AGN feedback in galaxies with M _*  < 10 ^10 M _⊙ should be considered in galaxy evolution models.